H3K36 methyltransferase SDG708 enhances drought tolerance by promoting abscisic acid biosynthesis in rice. Issue 5 (25th March 2021) - Chen, Kai; Du, Kangxi; Shi, Yichen; Yin, Liufan; Shen, Wen‐Hui; Yu, Yu; Liu, Bing; Dong, Aiwu
Summary: Chromatin modifications play important roles in plant adaptation to abiotic stresses, but the precise function of histone H3 lysine 36 (H3K36) methylation in drought tolerance remains poorly evaluated. Here, we report that SDG708, a specific H3K36 methyltransferase, functions as a positive regulator of drought tolerance in rice. SDG708 promoted abscisic acid (ABA) biosynthesis by directly targeting and activating the crucial ABA biosynthesis genes NINE‐CIS‐EPOXYCAROTENOID DIOXYGENASE 3 ( OsNCED3 ) and NINE‐CIS‐EPOXYCAROTENOID DIOXYGENASE 5 ( OsNCED5 ). Additionally, SDG708 induced hydrogen peroxide accumulation in the guard cells and promoted stomatal closure to reduce water loss. Overexpression of SDG708 concomitantly enhanced rice drought tolerance and increased grain yield under normal and drought stress conditions. Thus, SDG708 is potentially useful as an epigenetic regulator in breeding for grain yield improvement.